Evidence that modulation requires sequences downstream of the promoters of two vir-repressed genes of Bordetella pertussis. - Beattie, D T (1990)
Gene expression in Bordetella pertussis is altered by environmental signals in a process called antigenic modulation. In the presence of modulating signals, expression of several known virulence factors and outer membrane proteins is coordinately reduced. From a bank of TnphoA fusions, we have identified five genes whose expression profiles are reciprocal of those of the major virulence determinants; that is, alkaline phosphatase activity is maximal during growth in the presence of the modulators nicotinic acid and MgSO4 (S. Knapp and J. J. Mekalanos, J. Bacteriol. 170:5059-5066, 1988). We have called these loci vir-repressed genes (vrg). Two of these gene fusions (vrg-6 and vrg-18) have been cloned in Escherichia coli, returned on low-copy-number plasmids to several strains of B. pertussis, and found to be regulated similarly to the fusions harbored on the chromosome. Deletions of the two vrg promoters were constructed and returned to B. pertussis. Regulation was maintained even when all but 24 nucleotides upstream of the vrg-18 initiation codon and 60 nucleotides upstream of the vrg-6 initiation codon were deleted, suggesting that cis-acting regulatory elements of these genes lie very near or within the coding region. We observed a 21-base palindromic sequence overlapping an 8-base direct repeat within the signal sequence coding region of vrg-6; insertion of a 6-bp linker in this region abolished regulation. These repetitive sequences are also at the site of greatest primary sequence identify between vrg-6 and vrg-18 and correspond to the signal sequence coding region. We propose models that involve recognition of this region by a vir-regulated gene product.